Strategi Pengelolaan Aset dan Sarana Prasarana untuk Mewujudkan Sekolah Ramah Anak Berbasis Pendidikan Islam - Pratiwi; Andriyani; Nurmalia Lusida (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Sekolah Ramah Anak (Child-friendly schools) place students as living subjects, so that the education process takes place in safe, clean and healthy conditions, with the guarantee that children's rights are respected and they are protected from violence. Setting up a child-friendly school requires adequate facilities and infrastructure. Educational facilities and infrastructure are school assets that must be well organized and managed to support quality education in schools. A school asset and infrastructure management strategy is needed. The purpose of this study is to explain the asset and infrastructure management strategies for the implementation of Islamic education-based child-friendly schools. This research uses qualitative research methods, namely documentary studies or literature studies conducted by reading and analyzing documentary sources in the form of journals, articles, and other documents related to the problem. Based on the research conducted, it is concluded that asset and infrastructure management strategies to realize child-friendly schools based on Islamic education include the application of sustainability principles in asset and infrastructure management, collaboration between stakeholders for effective management, and the use of technology and innovation in asset and infrastructure management.